Application of magnetic diagnostics to determine basic energy characteristics of plasma - Pashnev, V.K. (Вопросы атомной науки и техники, 2008)
Method of determination of plasma parameters and magnetic configuration of toroidal magnetic traps according to measurement results of magnetic fields of plasma currents out of volume of plasma confinement is implied now by magnetic diagnostics [1-3]. Rokosovskiy coil, diamagnetic loop and saddle coil are now used most often to determine macroscopic plasma parameters; they allow to determine longitudinal current magnitude and energy content of plasma in the confinement volume. The most important characteristics of plasma are energy confinement time of plasma tE and power W injected into plasma. Possibility to determine tE, W and Z (average charge value) values using sensors of magnetic diagnostics in stellarators is discussed. Показано, що при стрибкоподібній зміні потужності нагріву плазми за допомогою датчиків магнітною діагностики може бути визначена величина енергетичного часу життя плазми, потужність, що вводиться в плазму, средний заряд плазми, а також з'являється можливість з'ясування механізмів збудження струму в плазмі. Показано, что при скачкообразном изменении мощности нагрева плазмы с помощью датчиков магнитной диагностики может быть определена величина энергетического времени жизни плазмы tE, вводимая в плазму мощность W, средний заряд плазмы Z, а также появляется возможность выяснения механизмов возбуждения тока в плазме.